Promoting Autonomous Language Learners through Lesson Study Program: Vigotsky’s Social Constructivism Perspective - Hafirah Patang; Hamzah Machmoed; Nasmilah (Hasanuddin University, 2020)
The aim of the research is to analyze how Lesson Study promotes autonomous language learners viewed from social constructivism perspectives. This research applied qualitative method for data collection and analysis. The qualitative data were collected by trancribing the video recorded files of Lesson Study program. Data from video recorded files were analyzed by transcribing, classifying, coding, and categorizing to find out how Lesson Study promotes autonomous language learners viewed from Vigotsky’s social constructivism perspective. The result of the research indicates that the learners’ activities in Lesson Study cover all the three themes in Vigotsky’s social constructivism perspective, they are Social Interaction (SI), More Knowledgeable Others (MKO), Zone of Proximal Development (ZPD)